Kiều Vũ Linh
36 phút trước

(5/4 - x - 6/5)³ = -27/125

(1/20 - x)³ = (-3/5)³

1/20 - x = -3/5

x = 1/20 - (-3/5)

x = 13/20

Bình luận (0)
Kiều Vũ Linh
44 phút trước

(1,25 - 3/7 x)(-5/4 x + 14/9) = 0

1,25 - 3/7 x = 0 hoặc -5/4 x + 14/9 = 0

*) 1,25 - 3/7 x = 0

3/7 x = 1,25

x = 1,25 : 3/7

x = 35/12

*) -5/4 x + 14/9 = 0

-5/4 x = -14/9

x = -14/9 : (-5/4)

x = 56/45

Vậy x = 56/45; x = 35/12

 

Bình luận (0)
khanhha
khanhha
Phước Lộc
1 giờ trước (6:42)

(1) \(3\sqrt{5}=\sqrt{3^2\cdot5}=\sqrt{9\cdot5}=\sqrt{45}\)

(2) \(1,2\sqrt{5}=\sqrt{1,2^2\cdot5}=\sqrt{1,44\cdot5}=\sqrt{7,2}\)

(3) \(ab^4\sqrt{a}\) với ≥ 0

\(=\sqrt{a^2\left(b^4\right)^2a}=\sqrt{a^3\cdot b^8}\)

Bình luận (0)
khanhha
khanhha
Phước Lộc
1 giờ trước (6:34)

(1) \(\sqrt{18}+\sqrt{50}=\sqrt{2\cdot9}+\sqrt{2\cdot25}=3\sqrt{2}+5\sqrt{2}=8\sqrt{2}\)

(2) \(\sqrt{2}+\sqrt{8}+\sqrt{50}=\sqrt{2}+2\sqrt{2}+5\sqrt{2}=8\sqrt{2}\)

Bình luận (0)